Examination of the internal structure of the behavioural regulation in sport questionnaire among dancers - Hancox, J.; Quested, Eleanor; Viladrich, C.; Duda, J. (2015)
Within sport, physical education and dance literature there is inconsistency in how individuals' motivation regulations for engagement are statistically modelled. This has implications for the interpretation of results and the testing and advancement of theory. Furthermore, despite the popularity of dance, there is a paucity of research examining the correlates of dancers' motivation due to there being no dance-specific measure of motivation. Hence, the purpose of this study was twofold: first to examine the utility of the Behavioral Regulation in Sport Questionnaire (BRSQ [Lonsdale, C., Hodge, K., & Rose, E. A. (2008). The behavioural regulation in sport questionnaire (BRSQ): Instrument development and initial validity evidence. Journal of Sport & Exercise Psychology, 30, 323–355. Retrieved from http://journals.humankinetics.com/jsep]) for measuring motivation in dance contexts and, second, to explore the tenability of using different scoring protocols to model the motivation regulations. To address these aims, a comprehensive examination of the hypothesised factor structure of the BRSQ when completed by recreational (n = 344) and vocational (n = 868) dancers was conducted. The data demonstrated good fit to the BRSQ, and invariance across dance level (recreational and vocational), age (<18 and ≥18 years of age) and gender was supported. Findings support the use of the six-factor BRSQ in dance contexts. The tenability of employing alternative scoring protocols for modelling the motivation regulations is discussed.